Corporate Social Responsibility and Financial Performance of Some Selected Banks in Nigeria: An Empirical Analysis - Ibrahim Aliyu Gololo (The Millennium University Journal, 2016)
This study examines empirically the relationship between corporate social responsibility and financial performance of some selected banks in Nigeria with the use of secondary data, sourced from six (6) selected banks annual reports and accounts using Judgemental sampling in a population of fifteen (15) Banks. Financial summary between “2002-2011” i.e. ten (10) years period and NSE FACT Book were used to obtain data. The objective of this study is to examine the impact of banks financial performance on Corporate Social Responsibility. The study utilized multiple regressions for the analysis of collected data, findings from the analysis of selected banks show that financial performance (PAT, ROCE, EPS) have significant positive impact on corporate social responsibility, and the collinearity test show that there is no Multicollinearity between the independents variables. The Independent Variables are PAT, ROE, ROA, EPS and ROCE which constitute indicators of banks financial performance while the Dependent variables are Philanthropic, Economic, Legal and Ethical Responsibilities (CSR). It is recommended that Nigerian banks should embrace the culture of CSR and government should established laws and regulations to oblige financial institutions or rather banks in Nigeria to give adequate attention to social responsibility, social accounting and put in place strong mechanisms and institutions to monitor compliance and if possible determine the quantum amount of charitable contribution to be reported in their annual reports and accounts by providing index or range.